Effects of p‐ and n‐type Doping in Inorganic Fullerene MoS2 on the Hydrogen Evolution Reaction. Issue 11 (15th September 2016) - Chhetri, Manjeet; Gupta, Uttam; Yadgarov, Lena; Rosentsveig, Rita; Tenne, Reshef; Rao, C. N. R.
Abstract: In this report, a systematic study of the effects of p‐ and n‐type doping of the inorganic fullerene (IF) MoS2 on the efficiency of the hydrogen evolution reaction (HER) is described. Active edge site enriched IF‐MoS2, promoted by strategically introducing Nb (p‐type) and Re (n‐type) dopants (below 500 ppm), enables facile HER over a range of pH values. Experimental results suggest that although Nb‐doping on IF‐MoS2 leads to better electrocatalytic HER activity in an alkaline medium with an onset potential difference of 80 mV, Re‐doping gives excellent activity in an acidic medium. The present work presents a systematic study of HER activity by finely tuning the activity in different electrolyte media with varied pH values through deliberate doping of the parent catalyst with p‐ and n‐ type materials. The doped IF‐MoS2 catalysts exhibit excellent catalytic activity even with sea water as an electrolyte. Abstract : The doping effect : Reduction of overpotential in the electrocatalytic hydrogen evolution reaction and fine tuning of the hydrogen evolution activity over a range of pH values can be achieved by p‐ and n‐type doping of MoS2 inorganic fullerenes.